Writing by academics: a transactional and systems approach to academic writing behaviours. Issue 5 (2nd September 2016) - Kempenaar, Larissa Elisabeth; Murray, Rowena
ABSTRACT: The literature on academic writing in higher education contains a wealth of research and theory on students' writing, but much less on academics' writing. In performative higher education cultures, discussions of academics' writing mainly concern outputs, rather than the process of producing them. This key component of academic work remains under-theorized, and the exact nature of the challenge of academic writing is understated at best and misunderstood at worst. This paper offers a new approach to academic writing, based on a transactional and a systems model, which aims to understand academic writing practices. This paper offers a new explanation of the challenge of academic writing, defining factors that enable and inhibit academics' writing.